Aging backwards: fast track : 6 ways in 30 days to look and feel younger - Esmonde-White, Miranda (Aging Backwards, 2019)
A 30-day anti-aging program for rapid results using the fundamental movements and principles of the bestselling Aging Backwards, featuring an accelerated program for turning back the clock. The field of aging research has exploded with new clinical findings. Many misconceptions about aging -- including the beliefs that disease, immobility, and pain are inevitable -- have been debunked. Today, we know that the choices we make, from what we eat to how much and how we move, play a critical role in healthy aging. PBS fitness personality and bestselling author Miranda Esmonde-White created her breakthrough exercise program, Essentrics, more than twenty years ago. In that time, she has helped everyone from professional athletes to breast cancer survivors to weekend warriors heal and recover from injuries using her gentle Essentric stretching and exercise method that consists of movements that engage all of the body's muscles and connective tissues. In Aging Backwards: The Fast Track, Miranda offers readers systematic workouts to supplement and accelerate the original program, along with new information on the latest anti-aging science to help keep us strong, fully mobile, and looking and feeling young. Using her 30-day fast-track program, you'll see rapid results in increased mobility, strength, flexibility, body shape, pain relief and overall health. Aging Backwards: The Fast Track empowers everyone -- young and old, athletic or sedentary -- with the information and tools to slow down the clock and keep it there.